Pengaruh Model Pembelajaran Berbasis Masalah terhadap Hasil Belajar PKN - Darsono , (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2020)
This study aims to reveal the effect of the problem-based learning model on the learning outcomes of Civics students at SD N in the cluster of Ahmad Dahlan, Sruweng sub-district. This research is a quantitative research. The population in this study were all students at SD N in the Ahmad Dahlan cluster, Sruweng sub-district, while the sample in this study were fourth grade students at SD N in the cluster Ahmad Dahlan, Sruweng sub-district, totaling 89 students. Data collection used a questionnaire, and data analysis used a simple regression analysis technique. This study resulted in the conclusion that the Problem-Based Learning Model has a positive and significant influence on Student Civics Learning Outcomes in Public Elementary Schools in the Ahmad Dahlan Cluster, Sruweng District. This is evident from the value of Sig = 0.000 < α = 0.05. The value of the correlation coefficient (r2) = 0.277 or a contribution of 27.7%. Keywords: